Genetic diversity analysis in sponge gourd (Luffa aegyptiaca) - KOUSTHUBHA V P; ANITHA P; PRADEEP KUMAR T; FLEMINE XAVIER; BEENA V I (The Indian Journal of Agricultural Sciences, 2023)
Sponge gourd is versatile summer vegetable having potential applications across many sectors. Twenty sponge gourd genotypes were studied at the Department of Vegetable Science, College of Agriculture, Vellanikkara, Kerala Agricultural University, Thrissur, Kerala for the study of variability in morphological, yield and biochemical traits. Significant difference existed among the genotypes for all the characters under study. In general, Phenotypic Coefficient of Variation (PCV) was higher than Genotypic Coefficient of Variation (GCV) for all the traits evaluated, which indicated the influence of environment on these traits. High estimates of PCV and GCV were recorded for node number of the first staminate flower, number of primary branches per plant, number of fruits per plant, fruit yield per plant, calcium, iron and fibre content. High heritability coupled with high genetic advance as a per cent of the mean were evident in most of the morphological and biochemical traits which suggested the influence of additive gene action for controlling these traits. Genotypes IC-343160, IC-332319 and IC-312949 were high yielders. The sponge gourd genotypes were grouped into seven clusters based on Mahalanobis D2 statistics. Cluster VII had the highest number of genotypes (5) followed by cluster VI (4), and intra cluster distance was maximum in cluster VII. Inter cluster distance was maximum between cluster I and III. Therefore, for exploitation of heterosis, genotypes should be selected from cluster I and cluster III.